-3(x-7)+7x=4(x+6)

Simple and best practice solution for -3(x-7)+7x=4(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-7)+7x=4(x+6) equation:


Simplifying
-3(x + -7) + 7x = 4(x + 6)

Reorder the terms:
-3(-7 + x) + 7x = 4(x + 6)
(-7 * -3 + x * -3) + 7x = 4(x + 6)
(21 + -3x) + 7x = 4(x + 6)

Combine like terms: -3x + 7x = 4x
21 + 4x = 4(x + 6)

Reorder the terms:
21 + 4x = 4(6 + x)
21 + 4x = (6 * 4 + x * 4)
21 + 4x = (24 + 4x)

Add '-4x' to each side of the equation.
21 + 4x + -4x = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
21 + 0 = 24 + 4x + -4x
21 = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
21 = 24 + 0
21 = 24

Solving
21 = 24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3(2x-5)+2x=2(4x+1) | | 10=-3v+10 | | 3(2x-5)+2x= | | -4-k=-1+5k+3-6k | | 5+-11=-5+6t | | 8z-23=51+z | | -5x-9x=56 | | 28-x=7-4x | | -8-18=-162 | | -22=8+5x | | -7y=6 | | 1-7(-z+3)=-2(-9z-6)-3 | | -7w-13=-w | | 2x-3x=9 | | 5x^2+20=16x | | 5(x-1)=-20 | | -5=(p+2) | | 16z^2+8z-3=0 | | 7x-6=x^2 | | 5x^2-144=0 | | 5k+2=-13 | | 22x^2+123x+11=0 | | 4.5(x-1)=20 | | 5x+3y=34 | | 5x+3x=34 | | 169x^2-4=0 | | 7+2*4= | | 4x-3=-5x+6 | | 3-4x(-1)= | | (-5)=3-4(-5) | | 8=2k | | x^3*x= |

Equations solver categories